2010
DOI: 10.1167/10.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and modeling the strength of motion illusions perceived in static patterns

Abstract: The origin of motion illusions in simple black and white patterns such those as used by Op artists has been at the center of a lively scientific debate, relating motion processing mechanisms to involuntary eye movements that generate characteristic motion patterns. To overcome the limitations of using subjective ratings as a measure of illusory effects, we developed a new method to quantify the strength of the illusion for synthetic 'riloids' that were inspired by Bridget Riley's 'Fall'. In a 2AFC paradigm, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 42 publications
6
38
0
Order By: Relevance
“…The main finding of the study was that the strength of the motion illusion grows with the amplitude ( A ) and the spatial period (μ) of the wave-like undulations of the line gratings, but was unaffected by the spatial wavelength of the gratings (λ). In addition, we observed that the strength of the motion illusion was not influenced by the presence or absence of a fixation target (Zanker et al 2010). This latter finding provides an interesting opportunity to determine how the motion illusion relates to certain aspects of fixational eye movements.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…The main finding of the study was that the strength of the motion illusion grows with the amplitude ( A ) and the spatial period (μ) of the wave-like undulations of the line gratings, but was unaffected by the spatial wavelength of the gratings (λ). In addition, we observed that the strength of the motion illusion was not influenced by the presence or absence of a fixation target (Zanker et al 2010). This latter finding provides an interesting opportunity to determine how the motion illusion relates to certain aspects of fixational eye movements.…”
Section: Introductionmentioning
confidence: 87%
“…In addition to using a set of stimuli with the same three contrast mixtures as in Experiment 1, a second set was created in which the overall contrast of the pattern was strongly reduced (see Figure 5b) to test for the effects of the contrast of the pattern, which has been shown to strongly affect the motion illusion (Zanker et al 2010). By adding these low-contrast stimuli, the number of trials doubled to 72 (12 repetition of each of 6 contrast conditions).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations